Maddy Kettle the adventure of the Thimblewitch - Orchard, Eric (Marietta, GA Top Shelf Production, 2014)
Eleven-year-old Maddy loved working in her parents' bookstore, especially when joined by her pet flying toad Ralph. But that was before the mysterious Thimblewitch turned her mom & dad into kangaroo rats! Now Maddy's on the adventure of a lifetime. To save her parents, she'll need to sneak past an army of spider-goblins, scarecrow warriors, and much more. Fortunately, an assortment of new friends await, including the cloud cartographers Harry and Silvio, a bear and raccoon who explore the world in their moon-balloon. They'll help her along the way, but in the end, the fate of everyone will depend on Maddy's courage, compassion, and creativity.
Keywords: Girls; Toads; Imaginary places; Witches; Magic; Adventure fiction; Fantasy fiction; Graphic novels